Analisis Kinerja Perusahaan Sebelum dan Setelah Go Public - Achmad, Noor; Angelica, Suci (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Go public is share offering activity or other effects done by issuers. The problem which will be revealed is whether the company’s performance after becoming public company increases compared with its performance before becoming public company. The purpose of this study is to analyze whether there is an increase in firm’s performance before and after becoming public company in Indonesia Stock Exchange. In this study the author carried out analysis on the performance of PT Bakrie Telecom Tbk. and PT Mobile-8 Telecom Tbk. The analysis on the issuers was done due to they are included in the companies conducting public offering in 2006 and they form similar companies operating in telecommunication sector. The period studied is 2003 – 2009. The author got data concerning the research object from Money Market Reference Center and by downloading data from situs-IDX. The data obtained are in the form of a brief history of the two companies, the main activities of issuers, financial report in period 2003 – 2009, and stock price data in period 2006 – 2009. The method used is descriptive method. The research variables examined are firms’ performance before and after go public with indicators: liquidity ratios (current ratio, quick ratio, and cash ratio), debt ratios (debt ratio and debt to equity ratio), activity ratios (total assets turnover, fixed assets turnover, inventory turnover, accounts receivable turnover, working capital turnover, and accounts payable turnover), and profitability ratios (gross profit margin, operating profit margin, return on assets, return on capital employed, and return on equity). The result obtained from existing data analysis is PT Bakrie Telecom Tbk. and PT Mobile-8 Telecom Tbk. have better performance after go public. The analysis result of the two companies shows that the ratio after go public increases compared with before go public. Another analysis used is trend analysis. It’s the same with ratio analysis, analysis trend on PT Bakrie Telecom Tbk. shows higher trend if overall percentage compared with PT Mobile-8 Telecom Tbk. It can be concluded that PT Bakrie Telecom Tbk. has better performance than PT Mobile-8 Telecom Tbk. Keywords:companies’ performance; go public companies